THE MATERIAL DEVELOPMENT IN TEACHING ENGLISH FOR FIRST SEMESTER STUDENT AT PRIVATE UNIVERSITIES IN MALANG - Miftahul Hamim (Program Studi Pendidikan Guru Sekolah Dasar Fakultas Pendidikan Ilmu Pengetahuan Sosial dan Bahasa Institut Pendidikan Tapanuli Selatan, 2026)
Language proficiency is a necessity for a forum where scientific discussion and achievements as well as professional issues can be discussed. It emerged itself as the international language in different fields such as business and commerce, science and technology and international relations, medical environment, and education. In teaching and learning environment, Knowledge of material development is important for understanding the concept of improving educational environment. In teaching English, If lecturers do have the knowledge of this, they will be better in understanding the importance of each design they are utilizing in teaching the class and how it generates to units which lead to the successful goals of teaching and learning. This research aims to deliver the process of material development in teaching English for first semester student at Private universities in Malang to match student^s need of English acquisition. Through qualitative research method, it was found that there were three processes of material development they are adopting, developing, and adapting the material.